2021
DOI: 10.1177/11033088211027412
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the COVID-19 Control Measures on Widening Educational Inequalities

Abstract: COVID-19 has resulted in a global public health crisis. Measures adopted by governments across the world to reduce transmission have resulted in the closure of educational institutions and workplaces and reduced social interaction. The aim of the article is to reflect on the consequences of the COVID-19 global pandemic for the lives of young people from different social groups, with a special focus on education. It is a desk-based review of empirical research that has emerged in the wake of COVID-19 that has e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 34 publications
1
24
0
3
Order By: Relevance
“…The non-impact of immigrant families appears at odds with the literature regarding the impact of Covid-19 on migrant families. Darmody et al ( 2021 ), after pointing out the limited empirical evidence available on the impact of the COVID-19 pandemic on migrant/refugee/asylum-seeking children, highlight how the pandemic has widened pre-existing socio-economic inequalities (Dustmann et al, 2012 ; Entorf, 2015 ) and, in particular, educational inequalities, with dramatic consequences on vulnerable groups, such as children with special educational needs and migrant children. Similar conclusions are achieved by Bond ( 2020b ), in her systematic review on K-12 research on teaching and learning during the COVID-19 pandemic, who points out that, even though little research has focused on migrant students, support for migrants and refugees is one of the priority topics highlighted in literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-impact of immigrant families appears at odds with the literature regarding the impact of Covid-19 on migrant families. Darmody et al ( 2021 ), after pointing out the limited empirical evidence available on the impact of the COVID-19 pandemic on migrant/refugee/asylum-seeking children, highlight how the pandemic has widened pre-existing socio-economic inequalities (Dustmann et al, 2012 ; Entorf, 2015 ) and, in particular, educational inequalities, with dramatic consequences on vulnerable groups, such as children with special educational needs and migrant children. Similar conclusions are achieved by Bond ( 2020b ), in her systematic review on K-12 research on teaching and learning during the COVID-19 pandemic, who points out that, even though little research has focused on migrant students, support for migrants and refugees is one of the priority topics highlighted in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions are achieved by Bond ( 2020b ), in her systematic review on K-12 research on teaching and learning during the COVID-19 pandemic, who points out that, even though little research has focused on migrant students, support for migrants and refugees is one of the priority topics highlighted in literature. Amongst the reasons that led to this worsening of the situation of student migrants forced to home-schooling during the pandemic, the literature highlights several factors, including the educational attainment of their parents, who are less familiar with the curriculum and with the host country language (Smyth et al, 2009 ; Lehmann et al, 2021 ); the lack of educational technology and, accordingly, reduced opportunities to engage in online education (Bayrakdar and Guveli, 2020 ; Popyk, 2020 ; Primdahl et al, 2020 ; Save The Children, 2020 ); the scarce availability of a quiet place to study (Kluge et al, 2020 ; Darmody et al, 2021 ; Lehmann et al, 2021 ); the socioeconomic factors that generally penalize migrants (Dustmann et al, 2012 ), which were found to be dramatic during the pandemic and lockdown periods (Kluge et al, 2020 ); the negative impact on learning engagement and academic progress of students (Mohan et al, 2020 ; Darmody et al, 2021 ; Lehmann et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To prowadzi do spirali nierówności i biedy. Trzeba pamiętać, że skutki luki edukacyjnej, braku wiedzy będą trwałe, konsekwencje kryzysu ekonomicznego są możliwe do przezwyciężenia, kryzysu edukacyjnego -niekoniecznie (Darmody, Smyth and Russell, 2021).…”
Section: Pandemia I Edukacjaunclassified
“…The non-impact of immigrant families appears at odds with the literature regarding the impact of Covid-19 on migrant families. Darmody et al (2021), after pointing out the limited empirical evidence available on the impact of the COVID-19 pandemic on migrant/refugee/asylum-seeking children, highlight how the pandemic has widened pre-existing socio-economic inequalities (Dustmann et al, 2012;Entorf, 2015) and, in particular, educational inequalities, with dramatic consequences on vulnerable groups, such as children with special educational needs and migrant children. Similar conclusions are achieved by Bond (2020b), in her systematic review on K-12 research on teaching and learning during the COVID-19 pandemic, who points out that, even though little research has focused on migrant students, support for migrants and refugees is one of the priority topics highlighted in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions are achieved by Bond (2020b), in her systematic review on K-12 research on teaching and learning during the COVID-19 pandemic, who points out that, even though little research has focused on migrant students, support for migrants and refugees is one of the priority topics highlighted in literature. Amongst the reasons that led to this worsening of the situation of student migrants forced to home-schooling during the pandemic, the literature highlights several factors, including the educational attainment of their parents, who are less familiar with the curriculum and with the host country language (Smyth et al, 2009;Lehmann et al, 2021); the lack of educational technology and, accordingly, reduced opportunities to engage in online education (Bayrakdar and Guveli, 2020;Popyk, 2020;Primdahl et al, 2020;Save The Children, 2020); the scarce availability of a quiet place to study (Kluge et al, 2020;Darmody et al, 2021;Lehmann et al, 2021); the socioeconomic factors that generally penalize migrants (Dustmann et al, 2012), which were found to be dramatic during the pandemic and lockdown periods (Kluge et al, 2020); the negative impact on learning engagement and academic progress of students (Mohan et al, 2020;Darmody et al, 2021;Lehmann et al, 2021).…”
Section: Discussionmentioning
confidence: 99%